PENDEKATAN MODAL SOSIAL DALAM PENETAPAN UPAH MINIMUM BERDASARKAN WILAYAH PEMBANGUNAN ADAT (SOCIAL CAPITAL APPROACH IN MINIMUM WAGE DETERMINATION BASED ON THE ADAT DEVELOPMENT AREAS) - Wanggai, Lodewijk L. (Melanesia : Jurnal Ilmiah Kajian Bahasa dan Sastra, 2018)
This study aims to reveal the parameters that are understood in social capital as trust, network, norm, and value in the social community approach of the minimum wage determination policy policy based on 5 (fve) customary development areas: Tabi/Mamta, Saireri, Ha-Anim, La-Pago, and Me-Pago in Papua Province based on local wisdom (local wisdom). With the approach used is the positivist paradigm in the application of ethnographic methods, which is based on the understanding of ontology as an effort to reveal the truth of reality and social facts from the empirical side of labor development from the aspect of protection and supervision, which is categorized from wage understanding disputes as a reward and interpret the minimum wage as safety net, welfare improvement, and minimum wage as a standard. Wage councils are a representation of the representation of non-structural tripartite elements, which have the duty and function of providing advice and consideration, with some indicators such as; components of decent living needs, regional inï¬‚ation rate, productivity, and economic growth to the Governor in the form of a recommendation text before the determination of the Provincial Minimum Wage.